2022
DOI: 10.1177/21925682221148685
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Work-Related Neck Pain Among Spine Surgeons

Abstract: Study Design Cross-sectional survey. Objectives This study aimed to investigate work-related neck pain among AO spine surgeons in different regions by estimating its prevalence, predictors, consequences, and management methods. Methods A cross-sectional survey of 411 spine surgeon members of AO spine was conducted during March–May 2021, using the Modified Nordic Questionnaire and the Neck Disability Index. Data on neck pain experience during the last 12 months and its consequences and risk factors were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Several studies have been carried out regarding neck disorders among surgeons using endoscopes. 28 29 30 31 These studies serve as meaningful analogies for our research. In the past, line workers handled high voltage electric lines with insulated gloves, but recently, they have been using insulating sticks.…”
Section: Discussionmentioning
confidence: 86%
“…Several studies have been carried out regarding neck disorders among surgeons using endoscopes. 28 29 30 31 These studies serve as meaningful analogies for our research. In the past, line workers handled high voltage electric lines with insulated gloves, but recently, they have been using insulating sticks.…”
Section: Discussionmentioning
confidence: 86%
“…Within these 11 articles, six studies collected surgeonreported data derived from 2641 survey responses. 1,[9][10][11][12]14 All 6 survey studies were administered as online questionnaires, largely focused on specific spine-related societies/organizations (Tables 2 and 3). Forst et al and Riccio et al, administered their survey to spine surgeons who were members of the North American Spine Society in 2006 and 2020, respectively.…”
Section: Surveysmentioning
confidence: 99%
“…Several studies have found reduced CSA in muscles such as multifidus, semispinalis, and longus coli in individuals with chronic neck pain [17,27,28]. In the early stages of neck pain, patients may experience slight disruptions in their daily activities [29,30]. Zabihhosseinian et al [31] found that individuals with low neck pain experienced challenges while raising their shoulder due to fatigue in the neck muscles compared with healthy subjects.…”
Section: Introductionmentioning
confidence: 99%